Dynamic nuclear polarization of biocompatible 13C-enriched carbonates for in vivo pH imaging. Issue 14 (21st January 2016) - Korenchan, D. E.; Flavell, R. R.; Baligand, C.; Sriram, R.; Neumann, K.; Sukumar, S.; VanBrocklin, H.; Vigneron, D. B.; Wilson, D. M.; Kurhanewicz, J.
Abstract : High concentrations of hyperpolarized 13 C-bicarbonate are generated via rapid hydrolysis of highly polarizable, low-toxicity carbonate precursors. Abstract : A hyperpolarization technique using carbonate precursors of biocompatible molecules was found to yield high concentrations of hyperpolarized 13 C bicarbonate in solution. This approach enabled large signal gains for low-toxicity hyperpolarized 13 C pH imaging in a phantom and in vivo in a murine model of prostate cancer.